Edukacja młodzieży chłopskiej w Galicji doby autonomicznej - Meissner, Andrzej (Biuletyn Historii Wychowania, 2007)
The paper deals with the following questions: the conditions of education of peasant sons, the educational opportunities on an elementary, secondary and higher level as well as the results of this process. In Galicia, especially after it had gained autonomy, there opened real possibilities for learning for peasant children on all levels of education. The offered education was at a very good level, and what is most important in the Polish schools by Polish teachers. Most widespread was compulsory education in folk schools. The secondary school, which originally had an elite character, was becoming ever more democratic in the course of time, the fact demonstrated by a significant proportion of rural youth which in some gymnasiums reached 8-90%. Higher studies were also available for rural youth. In Galicia, when it enjoyed autonomy, 45,4% of pheasant sons studied in the Faculty of Law of the Jagiellonian University, in the Faculty of Philosophy 28,7%, in the Faculty of Theology 18,7% and in the Faculty of Medicine 7,5%. All in all, about 3800 persons of peasant origin completed their studies, which constituted 17,6% of all students. However, education was obtained at the price of many sufferings and with huge physical effort. The graduates of alician schools originating from rural environment were characterized by great diligence and an aspiration for professional success. In the second half of the 19th century, there began the process of formation of the Galician intelligentsia of peasant descent. The sons of peasants came to occupy high-ranking posts in various professions, they were prominent representatives of Polish science, actively participated in the educational, cultural, social and political life.